The Role of Proenkephalin in Predicting Renal Dysfunction and Mortality in Septic Patients Admitted to the Emergency Department and Intensive Care Unit: A Narrative Review - Christos Verras; Ioannis Ventoulis; Sofia Bezati; John Parissis; Effie Polyzogopoulou (Journal of Personalized Medicine, 2026)
Prompt diagnosis and treatment of sepsis and septic shock is crucial due to the persistently high rates of morbidity and mortality associated with the disease. Recently, research efforts have focused on identifying novel biomarkers that would detect, classify, and assess the severity of sepsis in a timely manner, thereby allowing for expeditious and precise treatment of sepsis and septic shock. Among these biomarkers, proenkephalin (PENK) has gained considerable attention. Accordingly, this narrative review aims to consolidate current evidence on the clinical utility of PENK in patients with sepsis and septic shock, with emphasis on its role as a biomarker of renal dysfunction and as a predictor of sepsis-associated acute kidney injury (AKI) and mortality in both the emergency department (ED) and intensive care unit (ICU) settings.